Hitler's daughter - French, Jackie (New York : HarperCollins, 2003)
After hearing a fictional tale about Hitler's daughter, Mark, an Australian boy, wonders what it would be like if someone he loved and trusted turned out to be evil.
Originally published: Australia : Angus & Robertson, 1999.
4.4
3-6
3-6
Wilson's Junior High School
Booklist
Keywords: Hitler, Adolf, -- 1889-1945 -- Family -- Juvenile fiction; Hitler, Adolf, -- 1889-1945 -- Family -- Fiction; Storytelling -- Fiction; Australia -- Fiction; Hitler, Adolf, -- 1889-1945 -- Family -- Fiction; Storytelling -- Fiction; Australia -- Fiction